Indonesian Maqasid Al-Syari’ah: A Study of Yudian Wahyudi's Thought - Muzammil, Shofiyullah; Waryani Fajar Riyanto; Nur Edi Prabha Susila Yahya (DINIKA : Academic Journal of Islamic Studies, 2023)
This article describes Yudian Wahyudi's thoughts regarding Maqasid al-Syari’ah as a method of solving contemporary problems in Indonesia. The primary data of this research was obtained from Yudian's writings about Maqasid al-Syari’ah. The secondary data were obtained from authoritative, up-to-date, and relevant literature sources. This study finds an Indonesian Maqasid al-Syari’ah theory, which is different from the Classical and Contemporary Maqasid al-Syari’ah. Indonesian Maqasid al-Syari’ah wants to harmonize between Maqasid al-Syari’ah (five primary needs or zharuriyyat al-khams) and IndonesianMaqasid (based on Pancasila). Maqasid al-Syari’ah Yudian's idea rests on four pillars, namely: tauhidul 'ulum (unity of knowledge) between Ayat Qur’aniyah, Kauniyah, and Insaniyah (zharuriyat ats-tsalasah) as the embodiment of the slogan al-Ruju' ila al-Qur'an wa al-Sunnah (Return to the Qur'an and Sunnah), the theory of pairing in Islamic law (ilahi-wad'i, absolute-relative, universal-local, eternal-temporary, and literal-meaning), method (Maqasid al -Syari'ah as an analytical knife or point of view to read the reality that is around us), and matters related to Indonesia. Meanwhile, Maqasid Indonesia is based on the five basic values of the goals of the Indonesian nation as embodied in Pancasila (Salam Pancasila): divinity (hifdz al-din), humanity (hifdz al-nafs), unity (hifdz al-nasl), deliberation and wisdom (hifdz al-’aql), and social justice (hifdz al-mal). The results of this study can have implications for the development and alignment factors of the Maqasid al-Syari’ah theory, which is unique to Indonesia. Indonesian Maqasid al-Syari’ah is a strengthening of the foundation of Usul al-Fiqh and Indonesian Fiqh.